Effects of social support on job burnout among police officers: Mediating role of psychological empowerment - Jiajia ZHANG; Santiago GASCÓN; Furong TANG; Hongguang LIU (环境与职业医学, 2023)
BackgroundThe high-pressure and high-risk nature of the police profession may consume individual resources and lead to job burnout.ObjectiveTo understand the current situation of police job burnout, and test potential mediating role of psychological empowerment between social support and job burnout. MethodsFrom May to October 2020, a questionnaire survey was conducted among police officers in cities A and B of Sichuan Province by convenience sampling. The Perceived Social Support Scale, Psychological Empowerment Scale, and Maslach Burnout Inventory-General Survey were used to evaluate social support, psychological empowerment, and job burnout respectively. Mediation effect of psychological empowerment on the relationship between social support and job burnout was tested using bias-corrected bootstrap method. ResultsOf the 483 questionnaires recovered, there were 461 valid questionnaires (95.44%). The M (P25, P75) scores of social support, psychological empowerment, and job burnout were 5.00 (3.50, 5.83), 3.25 (2.00, 4.25), and 3.61 (2.43, 3.88), respectively. The positive rate of job burnout was 93.92% (433/461), of which 42.51% (196/461) and 51.41% (237/461) of the participants were at mild to moderate and severe levels of job burnout respectively. The results of Spearman correlation analysis showed that social support and psychological empowerment were negatively correlated with job burnout (r=−0.265, −0.328, P<0.01), and social support was positively corrected with psychological empowerment (r=0.390, P<0.01). The Bootstrap test results showed that social support negatively affected job burnout (β=−0.193, P<0.001) and positively affected psychological empowerment (β=0.330, P<0.001). Psychological empowerment negatively affected job burnout (β=−0.212, P<0.001) and played a partial mediating role in the relationship between social support and job burnout, and the effect value was −0.070 (95%CI: −0.097, −0.047) that accounted for 36.27% of the total effect. ConclusionJob burnout is prevalent among the police officers. Social support has a negative effect on job burnout, and psychological empowerment plays a partial mediating role between social support and job burnout.